Identification of Breast Tumors With Image Processing Using Canny Edge Detection - Triwibowo, Deny Nughoro; Dewa, Bala Putra; Sumantri, R Bagus Bambang; Suryani, Riska (Peneliti Teknologi Teknik Indonesia, 2023)
Breast tumor is one of the leading causes of death in women worldwide. The term tumor is often used for all lumps found in the human body. The increase in the number of cases of breast tumors that occur each year is due to the absence of prevention or early detection. The research was carried out by utilizing the development of information technology to create a breast tumor detection system with digital image processing. The application system will process mammogram images to detect edges with the canny method and will be classified using the SVM method. The data used is 176 data obtained from the Kaggle dataset. The test results revealed that 64 patients were classified as having malignant breast tumors (M), and 113 did not have breast tumors (B), with a classification accuracy rate of 95%. From the results obtained, the application system is very good for the early identification of breast tumors.